Rethinking the concept of 'healing settlements' : water, cults, constructions and contexts in the ancient world : Roman Archaeology Conference 2016 : proceedings of the session of study (nr. 27), Sapienza University, Aula 'Partenone', 17th March 2016 - Bassani, Maddalena; Bolder-Boos, Marion; Fusco, Ugo, 1970- (Archaeopress Roman archaeology, 2019)
This volume brings together papers dealing with therapeutic aspects connected to thermo-mineral sites both in Italy and in the Roman Provinces, as well as cultic issues surrounding health and healing. The first part of the book consists of contributions that are focused on the numerous problems concerning the exploitation of curative springs and the settlement patterns at spa sites in terms of topography, infrastructure, architecture, cult, society and economy, emphasizing the particularities accompanying the use of beneficial sources and comparing them to that of common sweet waters. The papers in the second part of the volume are concentrated on religious aspects connected to health, fertility and healing, focusing especially on sites located at particular natural surroundings such as caves and water sources. Together, the contributions in this book give us an idea of the amount and quality of research currently being undertaken in different parts of the Roman world (and complemented by one paper on the Greek world) on the topic of health and healing associated with cults and salutiferous waters.